Study of Solute-Solvent Interaction Through Dielectrics and Densities Properties of 2-Butoxyethanol in 2-Ethoxyethnol At Different Temperature - Anil L. Tidar; P.W. Khirade (International Journal of Pharma and Bio Sciences, 2010)
The excess molar volume (vE), static dielectric deviation (âˆ†Ñ”), molar refraction (Rm), excess molar refraction (âˆ†Rm), Bruggeman factor (fB), Mean molar polarizability (α), and polarity have been calculated from experimental measured density (ρ), static dielectric constant (Ñ”) and refractive index (n) data of the binary mixtures of 2-Butoxyethnol (2-BE) with 2-Ethoxyethnol (2-EE) measured over the entire range of composition at 288.15, 298.15, 308.15 and 318.15 K. The excess properties were fitted to the Redlich-Kister (RK) polynomial equation to derive the adjustable parameters (Aj) and corresponding standard deviations ( ).Results regarding the intermolecular hydrogen bonding are discussed.